Simple, Inexpensive RNA Isolation and One‐Step RT‐qPCR Methods for SARS‐CoV‐2 Detection and General Use. Issue 4 (27th April 2021) - Graham, Thomas G.W.; Dugast‐Darzacq, Claire; Dailey, Gina M.; Darzacq, Xavier; Tjian, Robert
Abstract: The most common method for RNA detection involves reverse transcription followed by quantitative polymerase chain reaction (RT‐qPCR) analysis. Commercial one‐step master mixes—which include both a reverse transcriptase and a thermostable polymerase and thus allow performing both the RT and qPCR steps consecutively in a sealed well—are key reagents for SARS‐CoV‐2 diagnostic testing; yet, these are typically expensive and have been affected by supply shortages in periods of high demand. As an alternative, we describe here how to express and purify Taq polymerase and M‐MLV reverse transcriptase and assemble a homemade one‐step RT‐qPCR master mix. This mix can be easily assembled from scratch in any laboratory equipped for protein purification. We also describe two simple alternative methods to prepare clinical swab samples for SARS‐CoV‐2 RNA detection by RT‐qPCR: heat‐inactivation for direct addition, and concentration of RNA by isopropanol precipitation. Finally, we describe how to perform RT‐qPCR using the homemade master mix, how to prepare in vitro−transcribed RNA standards, and how to use a fluorescence imager for endpoint detection of RT‐PCR amplification in the absence of a qPCR machine In addition to being useful for diagnostics, these versatile protocols may be adapted for nucleic acid quantification in basic research. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Preparation of a one‐step RT‐qPCR master mix using homemade enzymes Basic Protocol 2 : Preparation of swab samples for direct RT‐PCR Alternate Protocol 1 : Concentration of RNA from swab samples by isopropanol precipitation Basic Protocol 3 : One‐step RT‐qPCR of RNA samples using a real‐time thermocycler Support Protocol : Preparation of RNA concentration standards by in vitro transcription Alternate Protocol 2 : One‐step RT‐PCR using endpoint fluorescence detection